Community learning centre program as an educational tool for rural community literacy development: community of Nasr Abad as a case study - Zolfaghari, Akbar; Sabran, Mohammad Shatar; Gill, Sarjit Singh; Ahmad, Nobaya (Universiti Putra Malaysia Press, 2009)
Literacy plays a key role in community development. Literate people improve their quality of life with less difficulty, and Iran is no exception. For this purpose, the government of Iran has invested a lot of human, innovation, natural, and social capitals for literacy development to improve the quality of life of its people after the Islamic Revolution. Various programs have been set up for this purpose. One of the main programs for literacy development is the Community Learning Centre Program (CLCP) and one of the communities that has joined the program is the community of Nasr Abad. Hence, the objective of this paper was to examine the role of the community learning centre program in the rural community literacy development in the community of Nasr Abad.